2020
DOI: 10.1101/2020.05.22.111302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential consequences of the red blood cell storage lesion on cardiac electrophysiology

Abstract: 36The red blood cell (RBC) storage lesion is a series of morphological, functional and metabolic 37 changes that RBCs undergo following collection, processing and refrigerated storage for clinical 38 use. Since the biochemical attributes of the RBC unit shifts with time, transfusion of older blood 39 products may contribute to cardiac complications, including hyperkalemia and cardiac arrest. 40We measured the direct effect of storage age on cardiac electrophysiology and compared with 41 hyperkalemia, a promine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Reilly et al 23 studied the electrophysiological effects of the transfusion done by older PRBCs with the effects of biochemical alterations in the stored blood including hyperpotassemia. They demonstrated that older blood products mostly affected cardiac electrophysiology due to the alterations in the electrolytes of the stored blood especially potassium.…”
Section: Discussionmentioning
confidence: 99%
“…Reilly et al 23 studied the electrophysiological effects of the transfusion done by older PRBCs with the effects of biochemical alterations in the stored blood including hyperpotassemia. They demonstrated that older blood products mostly affected cardiac electrophysiology due to the alterations in the electrolytes of the stored blood especially potassium.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalaemia represents a key component of the pRBC storage lesion in which biochemical, metabolic and structural alterations occur within pRBCs in a time-dependent fashion, with a 3.76-fold increase in potassium concentration observed after three weeks [17 & ]. An in-vitro study demonstrated a direct link between supernatant from pRBCs stored for longer periods, hyperkalaemia and adverse electrocardiogram changes [18].…”
Section: Key Pointsmentioning
confidence: 99%
“…2 Potassium is a predominant intracellular cation, but an extracellular concentration greater than 5.5 mEq/L has significant effects on cardiac rhythm, which may lead to cardiac arrest. 7 Stored PRBCs are depleted of ATP, which alters the cell membrane, resulting in hemolysis and dysfunction of cation transporters, including impairment of Na + /K + ATPase, 8 which leads to a progressive increase in extracellular K + in the PRBC unit supernatant. 9 Furthermore, gamma irradiation, which is used to prevent graft-versus-host disease, increases hemolysis, resulting in potentiated K + leakage.…”
mentioning
confidence: 99%